Dynamic Urban Modelling for Urban Growth Varieties and Transport : Building A Complex Dynamic Model - Abdul Hussein Bedewy, Baydaa; Hassan Alwan, Kareem; Kamel Fleeh, Moheeb (IOP conference series. Earth and environmental science, 2021)
The need for urban simulation is to improve understanding of urban development and to predict urban changes. The dynamics of urban systems seek to represent the evolutionary patterns of a city over time and space, and it is possible to reduce uncertainty and increase understanding of the urban system as it is a very complex system. An integrated and proactive approach has been developed to plan for growth and transportation for the city of Al-Diwaniyah. Which is based on the CA (Cellular Automata) and shows that the pathway of simulation results reveals the difference in the expansion of urban areas in all directions of the city. This study extended to future stages to (2049) through a dynamic model. It is complicated by using the certification authority (CA cell model) and the results show that the complex interaction between growth and transmission has been well handled by the model. The model has shown during the simulation period of reality and the future (2019-2049) with cellular modelling CA and the future scenario for prediction indicates that commercial and entertainment in Al-Diwaniyah city increased in (2049) and therefore cellular modelling was found to be the most suitable for use in simulating urban growth in areas with evidence of simulation of reality and its comparison with the averages of uses in the city’s basic plan, which determined a percentage of 2035 that was exceeded by reality in 2029. The simulation results show that Al-Diwaniyah will face enormous challenges in the field of transport and urban development in (2049) within the framework of the current trends scenario. The accelerated growth of the population that excelled the estimates of the basic plan by a large percentage, especially among the model, reached 2034 with a city area of 10805 hectares. While in the basic plan it was explained by 2035 the city reaches 10643 hectares, and from the observation of the stages of changing uses according to the basic plan for the city of Al-Diwaniyah. In fact, the reality excelled the proportions from 2009 until Now 2019, especially the city of Al-Diwaniyah, which is directed towards commercial activity and religious and recreational tourism investments. The study ended with the most important recommendations and proposals to improve the city’s reality and drew the researchers’ attention to the importance of the subject of the study.